Aplicación de bioformulados de rizobacterias y fertilizantes sobre el proceso de germinación y desarrollo vegetativo de arroz (Oryza sativa L) - Saltos Aviles, Jeyson David (2023)
Rice cultivation is economically important worldwide. The use of chemical fertilizers is used on a large scale causing a negative impact on the health of the soil and the environment. This research was carried out in the Microbiology and Molecular Biology laboratory of the "UTEQ". The objective of the study was to determine the application of rhizobacterial bioformulates and fertilizers on the process of germination and vegetative development of rice (Oryza sativa L). A completely randomized design (DCA) was used. Three strains of bacteria were used: Pseudomonas protegens, CHA0 Serratia marcescens, 3-8, Acinetobacter calcoaceticus, 2-12 and three bioformulates: Bioimpulse, BioQPGRs, PGPR4N, for the experiments on the germination process of Oryza sativa L, due to the effect of bioformulates. of rhizobacteria, root development, fertilizer response and rhizobacterial bioformulations on the agronomic development of Oryza sativa L. The CHA0 Pseudomonas protegens bacterium accelerated the germination process of Oryza sativa L. It increased the radicle length with an average of 9.5 cm. The bioformulated PGPR4N presented the highest percentage of seed germination of 65%, likewise in the root length it obtained 3.7 cm and hypocotyl length of 2.92 cm. The N+Bioimpulse treatment obtained greater efficiency in the vegetative development of the plants. The results obtained confirmed an efficient bacterial influence on seed germination, root system and vegetative development of the plant, rhizobacterial bioformulates could be used to improve crop yield and productivity by maintaining a sustainable ecosystem. Keywords: Oryza sativa L, Bioformulated, Rhizobacteria.